2020
DOI: 10.1177/1747954120970922
|View full text |Cite
|
Sign up to set email alerts
|

Sanctioning of breakdown infringements during the knockout stage of the 2019 rugby world cup

Abstract: The breakdown is a complex and dynamic facet of rugby union, often containing multiple players from each team. It is the responsibility of coaches and trainers to ensure players are prepared to comply with the World Rugby laws of the game to encourage safe and fair play between all participants. The aim of this study was to investigate player adherence and sanctioning of infringements at the breakdown during the knockout stages of the 2019 Rugby World Cup. Breakdown infringements according to World Rugby laws … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…However, this pattern was not evident during the 2019 Rugby World Cup. 15 In this study "head and shoulders below hips" was the infringement that occurred most.…”
Section: Andmentioning
confidence: 74%
See 1 more Smart Citation
“…However, this pattern was not evident during the 2019 Rugby World Cup. 15 In this study "head and shoulders below hips" was the infringement that occurred most.…”
Section: Andmentioning
confidence: 74%
“…Mitchell and Tierney 15 . Kraak et al 7 demonstrated that attacking teams accounted for 90% (1 895 of 2 111) of all illegal ruck cleanouts, at an average of 16 per match.…”
Section: Andmentioning
confidence: 99%
“…Another feature of try in the last 20 minutes was that there have many tries by switching from defense to attack. Tackle study includes the issue of preventive medicine and refereeing concerned dangerous play [37][38][39]. There has detailed study which the tackle height by defense would relate to off-load success and clean break by attack [40].…”
Section: Discussionmentioning
confidence: 99%
“…14 Nazarudin et al 15 believes refereeing a professional rugby match is a substantial challenge. A breakdown may occur up to 200 times in a single match, 8 where the referee must interpret and apply the laws of the game instantaneously. A single misjudgement could affect the outcome of the match.…”
Section: Introductionmentioning
confidence: 99%
“…7 A ruck is formed when one or more players from opposing teams are in contact, on their feet, and competing over the ball which is on the ground, in order to retain (attacking team) or regain (defending team) possession. 8 A 2018 study analysed 7393 physical interaction events in the Championship and Six Nations competitions and determined that 65% of collisions resulted in a ruck. 9 The importance of retaining possession at a breakdown and turning the ball over has been found to be a key performance indicator associated with team success.…”
Section: Introductionmentioning
confidence: 99%